People living with HIV/AIDS: appraisal on dental care in Salta, Argentina - Molina-Ávila, Ignacio; Villalobos, Mercedes; Caporaletti, María Laura; Cordero-Torres, Karina Lizzy (Revista Facultad de Odontología Universidad de Antioquia, 2020)
Introduction: many patients living with HIV-AIDS (PLHIV) feel discriminated due to their disease, both socially and in health centers, including dental care. However, no current studies are available in Argentina regarding the preferences of these patients when visiting a dentist, the places where they prefer to be treated, or if they disclose their HIV(+) status, among other situations. Objective: to determine PLHIV’s appraisal on dental care in Salta, Argentina. Methods: descriptive, cross-sectional study. The study population were subjects who attended the HIV/STIs Program in the Salta Province in the period June-September 2015. Sociodemographic data, underlying disease, and dental care were collected in a survey created for this purpose. Results: 200 PLHIV were surveyed. 54% were male aged 37 years in average (IQR 29.2-45), with a median period of disease evolution of 78 months (IQR 30-126). 78% of respondents consulted a dentist in the last two years and 60% did so in public institutions. 70% perceived that their dentist has some knowledge on HIV. 50.5% disclosed their serological status to the treating professional. 87% reported that there were no prejudices during the service provided. Of the 49.6% who did not disclose their diagnosis, 55% claimed fear of discrimination. Conclusion: although PLHIV’s appraisal of dental care was positive, with no prejudices in most cases, fear of discrimination is the main reason for not informing the dentist of their diagnosis. Interdisciplinary work would help PLHIV in comprehensive care, thus avoiding one more reason for non-adherence to treatment.